Estimasi Interval Kredibel Distribusi Normal Terpotong Kiri pada Data Waktu Sembuh Pasien Covid-19 - Putri Fardha Asa Oktavia Hans; Ardi Kurniawan; Sediono; Elly Ana; M. Fariz Fadillah Mardianto (J STATISTIKA: Jurnal Imiah Teori dan Aplikasi Statistika, 2022)
The Covid-19 pandemic has been declared a Public Health Emergency of International Concern. One of the government's efforts to get out of the epidemic is to conduct an analysis based on existing data. The purpose of this study was to estimate the credible interval of the left truncated normal distribution. The results of the estimated credible intervals obtained have an implicit form so that they are solved by using a numerical integral approach. The results of this study were applied to the recovery time of Covid-19 patients from the Jemursari Health Center Surabaya in the range of December 2020 to February 2021. Through left cutting, the parameter estimation process only uses data that is more than 10 days, so that 37 data is obtained from a total of 45 data. It was found that the average recovery time for left-cut Covid-19 patients was between 10.583 days to 11.087 days. Meanwhile, the variance of recovery time for Covid-19 patients is cut left between 1.706 days to 1.772 days.